Hypoglycaemic activity of ethanolic extract of Garcinia mangostana Linn. in normoglycaemic and streptozotocin-induced diabetic rats. Issue 1 (December 2016) - Taher, Muhammad; Tg Zakaria, Tg Muhamad Faris Syafiq; Susanti, Deny; Zakaria, Zainul
Abstract Background Various parts ofGarcinia mangostana Linn., including its pericarp, have been traditionally used to treat a variety of ailments. In an attempt to establish its medicinal value, the present study was carried out to determine the hypoglycaemic potential ofG. mangostana pericarp ethanolic extract (GME) using the streptozotocin-induced (STZ) diabetic rats. Methods GME at 2, 000 mg/kg was subjected to a single-dose acute toxicity test. Following this, the effect of GME (50, 100, and 200 mg/kg) on blood glucose level of normoglycaemic and STZ-induced diabetic rats was determined using single-dose (acute) and multiple-dose (subacute) approaches. Subsequent to the multiple-dose study, serum biochemical analysis and liver histopathological examination were also performed. Throughout the experiments, the effect of GME was compared against the standard hypoglycaemic drug, glibenclamide. Results GME was safe for oral consumption up to the dose of 2, 000 mg/kg. In both single- and multiple-dose studies, GME significantly (p  < 0.05) reduced the blood glucose level in normoglycaemic rats and STZ-induced diabetic rats when compared against the normal control group or diabetic control group, respectively. Moreover, GME also significantly (p  < 0.05) increased the rats' body weight in comparison to the diabetic control group in the multiple-dose study. GME also significantly (p  < 0.05) reduced the levels of certain biochemical parameters [i.e., triglycerides (TG), total cholesterol (TC), low density lipoprotein (LDL), very low density lipoprotein (VLDL), serum glutamic oxaloacetic transaminase (SGOT), serum glutamic pyruvic transaminase (SGPT), urea, and creatinine] while increased the others [i.e., high density lipoprotein (HDL) and total protein (TP)] when compared to the diabetic control group. Histopathological assessment of the collected liver revealed a mild increase in the population of β-cells in the diabetic rats. Conclusion GME exerts the hypoglycaemic activity possibly by increasing the population of insulin-producing β-cells. This activity could be attributed to the presence of antioxidant-bearing tannins like epicathecin, and xanthones like α-mangostin. Thus, the findings demonstrated that GME could be a potential candidate in the management of diabetes owing to its hypoglycaemic effect.